25 Years of Reticular Chemistry. Issue 45 (9th July 2021) - Freund, Ralph; Canossa, Stefano; Cohen, Seth M.; Yan, Wei; Deng, Hexiang; Guillerm, Vincent; Eddaoudi, Mohamed; Madden, David G.; Fairen‐Jimenez, David; Lyu, Hao; Macreadie, Lauren K.; Ji, Zhe; et al.
Abstract: At its core, reticular chemistry has translated the precision and expertise of organic and inorganic synthesis to the solid state. While initial excitement over metal–organic frameworks (MOFs) and covalent organic frameworks (COFs) was undoubtedly fueled by their unprecedented porosity and surface areas, the most profound scientific innovation of the field has been the elaboration of design strategies for the synthesis of extended crystalline solids through strong directional bonds. In this contribution we highlight the different classes of reticular materials that have been developed, how these frameworks can be functionalized, and how complexity can be introduced into their backbones. Finally, we show how the structural control over these materials is being extended from the molecular scale to their crystal morphology and shape on the nanoscale, all the way to their shaping on the bulk scale. Abstract : Reticular chemistry translates the precision and expertise of organic and inorganic synthesis to the solid state. The most profound innovation of the field has been the elaboration of design strategies for the synthesis of extended crystalline solids through strong directional bonds. This Review highlights the classes of reticular materials, their functionalization, and the introduction of complexity into their backbones.